2022
DOI: 10.20944/preprints202203.0058.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Needlestick and Sharp Injuries among Hospital Healthcare Workers: An Infection Control Challenge in Saudi Arabia

Abstract: Needlestick and other sharp injuries (NSIs) are critical occupational hazard for healthcare workers. Exposure to blood and body fluids through NSIs increases the risk of transmission of blood-borne pathogens among them. The objectives of this study were to estimate the one-year incidence of NSIs and investigate its associated factors among the healthcare workers in Saudi Arabia. A cross-sectional online survey was conducted between October and November 2021. A total of 361 healthcare workers participated in th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Hand hygiene has been one of the most important factors of infection control in a healthcare setting, according to a crosssectional survey in Saudi Arabia. The hand hygiene knowledge and perception of the HCWs showed that the majority had moderate knowledge (57.8%) with perception (73.4%) of hand hygiene (8). The HCWs who were trained on hand hygiene were more likely to have good/ moderate perceptions than those without training.…”
Section: Introductionmentioning
confidence: 95%
“…Hand hygiene has been one of the most important factors of infection control in a healthcare setting, according to a crosssectional survey in Saudi Arabia. The hand hygiene knowledge and perception of the HCWs showed that the majority had moderate knowledge (57.8%) with perception (73.4%) of hand hygiene (8). The HCWs who were trained on hand hygiene were more likely to have good/ moderate perceptions than those without training.…”
Section: Introductionmentioning
confidence: 95%